A Novel Non-invasive Approach for Measuring Upper Airway Collapsibility in Mice - Nishimura, Yoichi; Arias, Rafael S.; Pho, Huy; Pham, Luu Van; Curado, Thomaz Fleury; Polotsky, Vsevolod Y.; Schwartz, Alan R. (Frontiers in Neurology, 2018)
ABSTRACT Introduction: Invasive procedures were previously developed for measuring pharyngeal collapsibility in rodents during expiration, when declining neuromuscular activity makes the airway unstable. We developed a non-invasive approach for streamlining collapsibility measurements by characterizing responses in physiologic markers of dynamic expiratory airflow obstruction to negative nasal pressure challenges. Methods: Anesthetized mice were instrumented to monitor upper airway pressure-flow relationships with head-out plethysmography while nasal pressure was ramped down from ~+5 to -20 cmH2O over several breaths. Inspiratory and expiratory flow, volume and timing characteristics were assessed breath-wise. Pcrit was estimated at transitions in expiratory amplitude and timing parameters, and compared to gold standard PCRIT measurements when nasal and tracheal pressures diverged during expiration. Predictions equations were constructed in a development data set (n=8) and applied prospectively to a validation data set (n=16) to estimate gold standard PCRIT. Results: The development data demonstrated that abrupt reversals in expiratory duration and tidal volume during nasal pressure ramps predicted gold standard PCRIT measurements. After applying regression equations from the development to a validation dataset, we found that a combination of expiratory amplitude and timing parameters proved to be robust predictors of gold standard PCRIT with minimal bias and narrow confidence intervals. Conclusions: Markers of expiratory airflow obstruction can be used to model upper airway collapsibility, and can provide sensitive measures of changes in airway collapsibility in rodents. This approach streamlines repeated non-invasive PCRIT measurements, and facilitates studies examining the impact of genetic, environmental and pharmacologic factors on upper airway control.